Diversity and distribution of figs (Ficus: Moraceae) in Gianyar District, Bali, Indonesia - I Made Saka Wijaya; Made Ria Defiani (Society for Indonesian Biodiversity, 2021)
Abstract. Wijaya IDS, Defiani MR. 2021. Diversity and distribution of figs (Ficus: Moraceae) in Gianyar District, Bali, Indonesia. Biodiversitas 22: 233-246. Fig (Ficus) is an important species in tropical regions, but there is a lack of updated data on fig diversity in Bali. This study of fig diversity and distribution in Gianyar District, Bali, Indonesia was conducted to record the alpha-diversity of figs. The intensive exploration method was applied at seven locations representing the seven sub-districts of Gianyar. Habitats and coordinates were recorded, and the appropriate samples were preserved as dried or spirit specimens. The results showed that there were 23 identified species of figs from six subgenera: Ficus (1), Pharmacosycea (2), Sycidium (5), Sycomorus (5), Synoecia (2), and Urostigma (9). Based on location, three species had restricted distribution: F. fulva, F. tinctoria ssp. globosa, F. virens, and F. subcordata, whereas six species were adapted in every location: F. montana, F. hispida, F. septica, F. pumila, F. benjamina, and F. superba. The figs were primarily distributed near bodies of water, especially riverbanks.